Opportunities and Challenges of Generative AI in Cultural Introduction and Intercultural Communicative Competence Cultivation in International Chinese Language Education - Chen, Junyan; Chen, Jiawang; Li , Yingmei (Scientific Journal of Technology, 2025)
The rapid proliferation of Generative Artificial Intelligence (GenAI) represents a paradigm shift in educational technology, presenting profound implications for language pedagogy. This paper provides a theoretical exploration of the dual-faceted impact of GenAI on International Chinese Language (ICL) education, with a specific focus on two integral components: cultural introduction and the cultivation of Intercultural Communicative Competence (ICC). Traditionally, these areas have been fraught with challenges, including reliance on static materials, the risk of essentialism, and limited opportunities for authentic interaction. This paper posits that GenAI offers unprecedented opportunities to overcome these limitations by enabling the creation of dynamic, personalized cultural content, facilitating immersive and adaptive communicative simulations, and scaffolding the development of critical cultural awareness. Through these affordances, GenAI can transform cultural learning from a passive reception of facts into an active, dialogic process of discovery. However, the integration of this technology is not without significant challenges. This paper critically examines the inherent risks, including the promulgation of algorithmic bias and cultural stereotypes, the philosophical tension between simulated interaction and authentic lived experience, the new pedagogical demands placed upon educators, and the potential erosion of the teacher’s role as a nuanced cultural mediator. In conclusion, the paper argues against both uncritical techno-optimism and prohibitive techno-pessimism. Instead, it advocates for a human-centered pedagogical framework wherein GenAI serves as a powerful tool under the critical guidance of the educator. The teacher’s role evolves from a purveyor of knowledge to a facilitator of critical inquiry, an architect of learning experiences, and an ethical guide in the complex landscape of AI-mediated intercultural education. This study calls for further research into developing best practices and ethical guidelines for the responsible and effective integration of GenAI in nurturing globally competent speakers of the Chinese language.